Design and Build a Web-Based Digital Thrifting Product Marketing System at Muhhasecond - Vriska Ruli Amanda; Rizkysari Meimaharani; Ahmad Jazuli (International Journal of Science and Environment (IJSE), 2026)
The thrifting industry or the sale of used products that are suitable for use is growing in Indonesia, especially among the younger generation. However, most thrifting business actors still use manual marketing through social media, so market reach is limited, transaction recording is less systematic, and product data management is inefficient. This research aims to design and build a web-based thrift product marketing system on Muhhasecond as a solution to improve the effectiveness of promotions and sales processes. The developed system provides a structured product catalog, ordering features, and automatic management of sales data and reports for admins. The research method uses the Waterfall model, including needs analysis, design, implementation, testing, and maintenance. The expected result is a web-based application that is able to expand marketing reach, increase operational efficiency, and support the competitiveness of Muhhasecond's thrifting business in the face of digital developments.